2017
DOI: 10.1001/jamacardio.2016.5804
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body Mass Index With Cardiometabolic Disease in the UK Biobank

Abstract: The results of this study add to the burgeoning evidence of an association between higher BMI and increased risk of cardiometabolic diseases. This finding has relevance for public health policies in many countries with increasing obesity levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
172
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(191 citation statements)
references
References 33 publications
18
172
0
1
Order By: Relevance
“…Obesity traits were causally related to higher risk of T2D, in keeping with previous studies (6)(7)(8)(9)(10)(11)19,64). We could not detect a sex difference in risk of T2D from higher WHR or WHRadjBMI.…”
Section: Diabetessupporting
confidence: 89%
See 2 more Smart Citations
“…Obesity traits were causally related to higher risk of T2D, in keeping with previous studies (6)(7)(8)(9)(10)(11)19,64). We could not detect a sex difference in risk of T2D from higher WHR or WHRadjBMI.…”
Section: Diabetessupporting
confidence: 89%
“…All obesity traits increased risk of CAD in both sexes, with no difference detected in the magnitude of effect between women and men. The associations with risk of CAD in men and women combined are consistent with previous studies (4,(6)(7)(8)10,11,15,17). While observational studies have indicated that waist-related traits may be more strongly associated with cardiovascular disease in women than men, they have not been conclusive (15,17,76).…”
Section: Cardiovascular Diseasesupporting
confidence: 84%
See 1 more Smart Citation
“…32 People with obesity, as compared to those of a healthy weight are at increased risk for many serious diseases and health conditions affecting multiple organ systems. 33–35 “Recent data provides strong evidence for a causal role of higher BMI and risk of type 2 diabetes and hypertension, and evidence that BMI increases risk of coronary heart disease.” 36 Obesity is associated with an increase in CVD such as coronary artery disease and stroke as well as CVD risk factors such as hypertension and dyslipidemia. Obesity is also associated with prediabetes (when the blood glucose level is higher than normal) and type 2 diabetes.…”
Section: Impactmentioning
confidence: 99%
“…The underlying biological relationship between adiposity and health is complex (4), but the endocrinal (5), cardiometabolic (6,7) and other changes (8) associated with increased adiposity are themselves linked to substantial healthcare resource requirements (9). Increases in the mean and variance of adiposity, reflected in widely used measures of nutritional status such as body mass index (BMI -weight divided by the square of standing height) have led to important changes in the global distribution of adiposity (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%